On a coupled system of abstract differential equations similar to the thermoelasticity equations - Gershtein, L. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The study of a model system of differential equations arising from the dynamical problems of thermo elasticity is continued. The case of shifts of the general type is investigated. We employ the “commutant method” based on the properties of the operator Δ(A, B) = AB - BA.